Evaluation of the role of Shodhana (Purification) process in Croton tiglium seeds for reduction of toxic content - Meena, Ajay Kumar; Venkataraman, Poorna; Singh, Ravindra; Ganji, Kusuma; C, Murali Krishna; N, Srikanth (International Journal of Ayurvedic Medicine, 2021)
In Ayurvedic texts, Jayapala or croton tiglium seeds are well known as khumbini for its toxicity (severe purgative action) and are used for the treatment of constipation after shodhana (detoxification) of the seed with godugdha (cow milk). The oil content of the seeds was responsible for the purgative property, and its reduction enhances its medicinal usage. The presence of Crotonoside or iso-guanosine in seed extract was identified in HPTLC and quantified using high pressure liquid chromatography technique both before and after the purification process of the seed. The phytochemicals and physicochemical parameters of seeds were analyzed to find the level of changes in the processed seeds. The other chemical constituents of the seed extracts are studied using different techniques like HPTLC, HPLC, LC-MS, and GC-MS. The study has revealed that the detoxification process, as per classical texts, has shown an effective depletion in the quantity of crotonoside in processed seeds.